PENGARUH PENGETAHUAN MANAJEMEN DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI KECAMATAN KREJENGAN KABUPATEN PROBOLINGGO - Moeh. Gusaeri; Gunadi; Jamal Abdul Naser (Ar-Ribhu : Jurnal Manajemen dan Keuangan Syariah, 2022)
This study aims to determine and analyze the effect of management knowledge and career development on employee performance in Krejengan District, Probolinggo Regency. The method of determining the sample in this study used a saturated sample, where the total population in this study were all employees of the Krejengan District, Probolinggo Regency, namely 43 employees. This study uses quantitative methods to describe and explain the type of research used is descriptive research using quantitative methods and approaches. The data analysis method used multiple linear regression. Testing the hypothesis partially, Knowledge Management and career development affect employee performance in Krejengan District. Results that Knowledge Management and career development affect employee performance in Krejengan District, Probolinggo Regency. The results showed that 1) Management knowledge had a significant effect on employee performance, 2) Career development had a significant effect on employee performance, 3) Simultaneously, management knowledge and career development had a significant effect on employee performance